Effectiveness of acupuncture in the treatment of recurrent aphthous stomatitis - Rosario Abraham Iglesias; Kenia Casanova Sales; Niria Yusimi Reyes Desdin; Sara Elena Panizo Bruzón; Lidiana de la Caridad Fajardo Álvare (Revista Electrónica Dr. Zoilo E. Marinello Vidaurreta, 2016)
Background: patients frequently present suffering from recurrent aphthous stomatitis or aphthae, which are painful ulcerations of the buccal mucosa both in children and adults. Literature tells that acupuncture can be effective in those cases. Objective: to assess the effectiveness of acupuncture in the treatment of recurrent aphthous stomatitis in patients from the health area of “Romárico Oro” Polyclinic in Puerto Padre from January, 2013 to January, 2015. Methods: An intervention study was carried out in a sample of 240 diagnosed patients, treated in the place and time period mentioned above. From the sample, two groups were formed, with 120 patients each: the study one, for the treatment with acupuncture, and the control one, who received the conventional treatment. Time was assessed in days for the disappearance of pain and ulcer, as well as the adverse effects. Results: in 80 % of the patients of the study group (I) the pain disappeared between the second and the fourth day and in the control group (II) in 3,3 % at the second day and in 13,3 % at the fourth day; in group I the ulcer disappeared at the sixth day in 53,3 % and in group II only in 20,8 %. 100 % of the patients treated with acupuncture were cured at the sixth day. Conclusions: acupuncture was effective for the treatment of recurrent aphthous stomatitis; cure was quicker and did not produce any adverse effect.